Application of learning scenarios quality evaluation methods - Kurilovas, Eugenijus; Žilinskienė, Inga (Lietuvos matematikos rinkinys, 2011)
The paper is aimed to analyse the problems of evaluation of quality of learning scenarios. Multiple criteria analysis principles are applied to form learning scenarios quality model. Several alternativesof learning scenarios that are widely used in Europe are analysed in the paper. These alternatives are evaluated with the help of the created quality model and application of triangular and trapezoidalfuzzy numbers methods. Research results show that both these methods are applicable in practice while evaluating quality of learning scenarios alternatives, and their application shows in principlesimilar results while comparing different alternatives of learning scenarios.
Keywords: quality of learning scenario; evaluation; fuzzy numbers methods; multiple criteria analysis principles